Microplastics in Environment and Effects on Biota - Bozdaş, Kübra; Üstün, Gökhan Ekrem; Aygün, Ahmet (Tarım ve Orman Bakanlığı Su Yönetimi Genel Müdürlüğü, 2020)
Plastics are used in many different fields because they are light, cheap and easy to process and become one of the most important commercial materials of today. The use of plastics is increasing every year, and since most of these materials are disposable and their wastes are not managed well, it brings environmental pollution problem. Particles smaller than 5 mm and known as microplastics are formed as a result of the breakdown of plastics by different processes in nature or as a result of direct use such as microbonces, textile fibers. Microplastics are ubiquitous in nature and are of concern for ecosystems. Environmental problems related with microplastic and studies on this subject have become the focus of interest in the last decade. Microplastics into receiving water from different sources poses a threat to aquatic organisms and humans. In this study, microplastics in different environments and their effects on environment and human health were reviewed.